Estimating population persistence for at-risk species using citizen science data. (March 2020) - Crawford, Brian A.; Olds, Melanie J.; Maerz, John C.; Moore, Clinton T.
Abstract: Population persistence probability is valuable for characterizing risk to species and informing listing and conservation decisions but is challenging to estimate through traditional methods for rare, data-limited species. Modeling approaches have used citizen science data to mitigate data limitations of focal species and better estimate parameters such as occupancy and detection, but their use to estimate persistence and inform conservation decisions is limited. We developed an approach to estimate persistence using only occurrence records of the target species and citizen science occurrence data of non-target species to account for search effort and imperfect detection. We applied the approach to a highly cryptic and data-limited species, the southern hognose snake ( Heterodon simus ), as part of its USFWS Species Status Assessment, and estimated current (in 2018) and future persistence under plausible scenarios of varying levels of urbanization, sea level rise, and management. Of 222 known populations, 133 (60%) are likely extirpated currently (persistence probability < 50%), and 165 (74%) populations are likely to be extirpated by 2080 with no additional management. Future management scenarios that included strategies to acquire and improve habitat on currently unprotected lands with existing populations lessened the estimated rate of population declines. These results can directly inform listing decisions and conservation planning for the southern hognose snake by Federal, State, and other partners. Our approach – using occurrence records and auxiliary data from non-target species to estimate population persistence – is applicable across rare and at-risk species for evaluating extinction risk with limited data and prioritizing management actions. Graphical abstract: Unlabelled Image Highlights: At-risk species are often data-limited but in need of conservation decisions. Population persistence was estimated from target species occurrence records. Citizen science data of non-target species accounted for imperfect detection. A majority (60%) of target species populations are likely extirpated at present. Acquiring and improving lands with extant populations lessened population declines.